A Review on Solar Secondary Concentrator - Muhammad Faez Ali; Mohd Ruddin Ab Ghani; Chin Kim Gan; Syariffah Othman; Zanariah Jano; Tole Sutikno (Universitas Ahmad Dahlan, 2018)
Concentrating solar power (CSP) is a solar thermal technology that generates electricity from thermal energy through the sun.The electricitycan be generated with four different types of CSP technologies that include Parabolic Dish (PD) systems. In order to make this technology more practical, the efficiency of the solar technology should be improved.Solar concentration is one of the main aspects that can affect the system’sefficiency. This paper reviewed solar secondary concentrators and discussed their designs and performance. Besides, their strengths and weaknesses were compared. Generally, thesecondary concentrators couldincrease the solar concentration of the solar technologyup to 93 percent.